The potential of recombinant surfactant protein D therapy to reduce inflammation in neonatal chronic lung disease, cystic fibrosis, and emphysema. Issue 11 (11th November 2003) - Clark, H; Reid, K
Abstract : By lowering surface tension at the air-water interface in the surfactant deficient premature lung, exogenous surfactant replacement therapy for neonatal respiratory distress syndrome has been highly successful in decreasing mortality after preterm birth. It has emerged in recent years that surfactant components not present in current surfactant formulations—particularly surfactant associated proteins A and D (SP-A and SP-D)—have additional roles in host defence distinct from the surface tension lowering effects of surfactant. SP-A and SP-D are calcium dependent carbohydrate binding proteins of the innate immune system important in the first line defence of the lung against microorganisms and in the control of lung inflammation. This review addresses the possibility that recently developed recombinant forms of SP-D could be useful therapeutically in attenuating inflammatory processes in neonatal chronic lung disease, cystic fibrosis, and emphysema.